THE EFFECT OF INDIVIDUAL MUSICAL INSTRUMENT STUDY HABITS OF FINE ARTS HIGH SCHOOL CELLO STUDENTS ON MUSICAL INSTRUMENT PERFORMANCE SELF-EFFICACY BELIEF - Ceren ALBAYRAK (Fırat University, 2021)
The purpose of this research is to examine the effect of individual musical instrument study habits of Fine Arts High School cello students on musical instrument performance self-efficacy belief. In this research descriptive general survey model was used. The sample of the research is comprised of 128 cello students studying at 1st, 2nd, 3rd, 4th grades of 14 Fine Arts High School chosen with maximum variation sampling method of purposive sampling methods from several provinces located in 7 regions of Turkey.As data collection tool, firstly, “Personal Information Form” was used to obtain information about students demographic characteristics. In order to determine musical instrument study habits related to individual musical instrument subject,“Individual Musical Instrument Study Habits Scale” developed by Küçükosmanoğlu, Babacan, Babacan and Yüksel (2016) in 2014-2015 Academic Year and in order to determine musical instrument performance self-efficacy levels, “Musical Instrument Performance Self-Efficacy Belief Scale” dveloped by Girgin (2015) were used. The effect of individual musical instrument study habits of cello students participating in the research on musical instrument performance self-efficacy belief was examined in terms of several variables. It was determined that the effect of individual musical instrument study habits of Fine Arts High School cello students on musical instrument performance self-efficacy belief was positve. When we examined the effect of individual musical instrument study habits of Fine Arts High School cello students on musical instrument performance self-efficacy belief according to the variables, it was determined that there were significant differences in gender and study time variables and no differentiation in the variables of their class levels and the region they study in.